The development and maintenance of mental toughness in the world's best performers - Connaughton, D.; Hanton, S.; Jones, G. (The Sport Psychologist, 2010)
Eleven superelite participants (7 performers, 2 coaches and 2 sport psychologists) were interviewed regarding the development and maintenance of mental toughness. Findings revealed that this process occurred over four distinct career phases: three developmental phases, and one maintenance phase. Factors influencing development and maintenance included: skill mastery, competitiveness, successes, international competitive experience, education and advice, the use of psychological skills, access to an understanding social support network, and reflective practice. In addition, positive and negative critical incidents were perceived by participants to act as catalysts in initiating or enhancing specific components of mental toughness. Practical implications highlight the importance of a mental toughness attitude/mindset to development, while future directions are discussed in relation to measurement and intervention strategies.